Between Real and Ideal : The Course of Otto Ludwig's Development as a Narrative Writer - McClain, William H. (University of North Carolina studies in the Germanic languages and literatures, 2020)
Otto Ludwig, nineteenth-century German novelist and critic, originated the term poetic realism. In this excellent study, Ludwig's prose is sympathetically and thoroughly examined and a clear account of the evolution of German fiction after Romanticism is presented. Taking Ludwig's narrative works together with his literary criticism, McClain shows how the author attempted to blend the real and the ideal to reach the goal of poetic realism as he envisioned it.